The inhibitory impact of various total body irradiation doses on the hematopoietic system of mice - Hui Xu; Jinwang Zhang; Hexiao Zhang; Ming Yang; Wenshan Zhang; Wei Wang; Chaoqun Wang; Yiran Zhang; Zhongxiang Jiao; Yingdai Gao; Yinghui Li (Blood Science)
Irradiation with X-rays has been widely utilized in the clinical treatment of solid tumors and certain hematopoietic malignancies. However, this method fails to completely distinguish between malignant and normal cells. Prolonged or repeated exposure to radiation, whether due to occupational hazards or therapeutical interventions, can cause damage to normal tissues, particularly impacting the hematopoietic system. Therefore, it is important to investigate the effects of total body irradiation on the hematopoietic system of mice and to compare the inhibitory effects of various doses of irradiation on this system. In this study, we primarily employed flow cytometry to analyze mature lineage cells in the peripheral blood, as well as immature hematopoietic stem and progenitor cells (HSPCs) in the bone marrow and spleen. Additionally, we evaluated the multilineage differentiation capacity of HSPCs through colony-forming cell assays. Our results indicated that peripheral B and T cells demonstrated increased sensitivity to irradiation, with significant cell death observed 1-day post-irradiation. Common lymphoid progenitor cells exhibited greater radiotolerance compared to other progenitor cell types, enabling them to maintain a certain population even at elevated doses. Moreover, notable differences were observed between intramedullary and extramedullary hematopoietic stem cells and common lymphoid progenitor cells regarding the extent of damage and recovery rate following irradiation. The multilineage differentiation capacity of HSPCs was also compromised during radiation exposure. In conclusion, different types of mature blood cells, along with immature HSPCs, exhibited varying degrees of sensitivity and tolerance to irradiation, resulting in distinct alterations in cell percentages and numbers.